O Serviço Social e a avaliação de impacto na gestão de programas e projetos empresariais - Scagnolato, Ana Lúcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The thesis presents analyses and reflections on Social Responsibility. The object of study is the evaluation of the impact on business program and project management. The objective of this study is to understand in order to explain the impacts on beneficiaries of programs/projects developed by a steel industry multinational located in Piracicaba, state of São Paulo. With an encompassing multi-disciplinary bibliography, it addresses the historical process of Social Responsibility in Brazil and it evaluates the impact, a fundamental part of social management, on the organization. The field investigation is supported by guidelines from the Social-Environmental Management research group and Interfaces with the Social Issue Expressions (GESTA), part of the Social Services Course at the College of Human and Social Sciences at UNESP, Franca Campus. The information obtained in interviews, through semi-structured forms, characterizes the profiles of subjects and institutions/entities with quantitative data and, through qualitative data, how those interviewed are, act, think and do, present in the testimonies, and guided by empirical categories. These express conflict, uncertainty, doubt and a lack of knowledge about the programs/projects in which they participate. The unanimous satisfaction of the beneficiaries is revealed in their speech. However, this is accompanied by an uncritical analysis, without commitment and engagement on the part of the subjects, elucidating resistance to change, founded on the non-recognition of freedom and critical power. This is possibly motivated by the condition of vulnerability and exclusion, which evidences the distancing between the actual and ideal result of social programs/projects. This process demands the political involvement of local organizations, including the company, in the sense of stimulating and monitoring the political participation of all social players...

Astratto: La tesi presenta analisi e riflessioni riguardo la questione della Responsabilità Sociale, avendo come obiettivo di studio la valutazione di impatto nella gestione di programmi e progetti corporativi. L’obiettivo di questo studio è capire per spiegare gli impatti causati nei beneficiari dei programmi/progetti sviluppati da una multinazionale del settore siderurgico, localizzata a Piracicaba, interno di San Paolo. Con bibliografia multidisciplinare estesa, tratta il processo storico della Responsabilità Sociale in Brasile e la valutazione di impatto, parte fondamentale della gestione sociale, nella sfera organizzativa. L’indagine di campo si appoggia in orientamenti del gruppo di ricerca Gestione Socio ambientale e le Interfaccia con l’Espressioni della Questione Sociale (GESTA), integrato al Corso di Servizio Sociale della Facoltà di Scienze Umane e Sociali, dell’UNESP, Campus di Franca. Le informazioni ottenute nelle interviste, per mezzo di formulari semistrutturati, caratterizzano con dati quantitativi il profilo delle persone e delle istituzioni/entità e, per mezzo dei qualitativi, il modo da essere, agire, pensare e fare degli intervistati, presenti nelle deposizioni, orientatori delle categorie empiriche. Essi esprimono conflitto, incertezza, dubbio e mancanza di conoscenza sui programmi/progetti nei quali hanno partecipato. La soddisfazione unanime dei beneficiari si rivela nelle parole, accompagnata, però, da analisi acritica, senza compromesso e partecipazione attiva da parte delle persone, delucidando resistenza al cambio, regolata nel non riconoscimento della libertà e del potere della critica, possibilmente motivati dalla condizione di vulnerabilità ed esclusione il che mette in evidenza il distanziamento fra il risultato reale e ideale dei programmi/progetti sociali. Questo processo richiede il coinvolgimento politico delle organizzazioni locali, fra loro, l’azienda...

A tese apresenta análises e reflexões sobre a questão da Responsabilidade Social, tendo como objeto de estudo a avaliação de impacto na gestão de programas e projetos corporativos. O objetivo deste estudo é compreender para explicar os impactos provocados nos beneficiários dos programas/projetos desenvolvidos por uma multinacional do setor siderúrgico, situada em Piracicaba, interior de São Paulo. Com bibliografia multidisciplinar abrangente, aborda o processo histórico da Responsabilidade Social no Brasil e a avaliação de impacto, parte fundamental da gestão social, na esfera organizacional. A investigação de campo se apoia em orientações do grupo de pesquisa Gestão Socioambiental e as Interfaces com as Expressões da Questão Social (GESTA), integrado ao Curso de Serviço Social da Faculdade de Ciências Humanas e Sociais, da UNESP, Campus de Franca. As informações obtidas nas entrevistas, por meio de formulários semiestruturados, caracterizam com dados quantitativos o perfil dos sujeitos e das instituições/entidades e, através dos qualitativos, o modo de ser, agir, pensar e fazer dos entrevistados, presentes nos depoimentos, norteadores das categorias empíricas. Estas expressam conflito, incerteza, dúvida e falta de conhecimento sobre os programas/projetos aos quais participaram. A satisfação unânime dos beneficiários revela-se nas falas, acompanhada, porém, de análise acrítica, sem comprometimento e engajamento por parte dos sujeitos, elucidando resistência à mudança, pautada no não reconhecimento da liberdade e do poder da crítica, possivelmente motivados pela condição de vulnerabilidade e exclusão o que evidencia o distanciamento entre o resultado real e ideal dos programas/projetos sociais. Este processo demanda o envolvimento político das organizações locais, dentre elas, a empresa, no sentido de estimular e monitorar a participação política de todos os atores sociais. Estes resultados...
Keywords: Serviço social - Administração; Responsabilidade social da empresa; Associações sem fins lucrativos; Trabalho profissional - Aspectos sociais; Associações, instituições, etc - Projetos; Social service